Формирование ДПК на участках, содержащих особые точки - Гавриленко, Евгений Андреевич; Гавриленко, Євген Андрійович; Havrylenko, Yevhen; Холодняк, Юлия Владимировна; Холодняк, Юлія Володимирівна; Kholodniak, Yuliia (МДПУ ім. Б. Хмельницького, 2018)
RU: В работе рассматривается задача формирования участков дискретно представленной кривой, которые содержат особые точки. Положение особой точки определяется внутри области возможного решения задачи. UK: У роботі розглядається задача визначення та класифікація ділянок дискретно представленої кривої, які містять особливі точки. Положення особливої точки визначаються всередині області можливого розв’язку задачі. EN: The problem of determining and classifying segments of a discrete presented curve that contain singular points is considered in this work. The position of the singular point are determined within the area of possible solution of the problem.
Keywords: дискретно представленная кривая; особая точка; гранная полярная поверхность; область расположения кривой; дискретно представлена крива; особлива точка; області розташування кривої; гранна полярна поверхня; discretely presented curve (DPC); a singular point; a region of the curve; a polished polar surface